Nutrition Metabolism and Infections. Issue 3 (19th September 2021) - Yang, Fang; Yang, Yi; Zeng, Lingchan; Chen, Yiwei; Zeng, Gucheng
Abstract : Abstract: Infection and nutrition are intricately interacted and further influence human health. Infections are a worldwide health problem and malnutrition plays a significant role in the emergence of infection. Growing evidence suggests that the optimization of dietary nutrients intake is crucial in maintaining systemic immunity and may help improve resistance to infections. In this review, we explore a wide range of topics including interactions between nutrients and various infectious diseases. We also discuss the role of diet-induced gut microbiota in the infection-nutrition cycle and review how dietary-microbiome crosstalk may affect disease development and progression, which may provide an attractive option to the design of a diet leading to favorable outcomes in the future. We will also present evidence and propose mechanisms of nutrients that may specifically modulate host immunity and metabolism to infectious pathogens and also cover its influence on nutrition, focusing on immuno-nutrients. We provide representative nutrients in the present review based on their intensive studies and wide acceptance of their immuno-modulating properties. Moreover, the efficacy and translational cost of their plausible utility to be anti-infective nutrients are also reviewed. Finally, we highlight the current progress and challenges to gain a better understanding of the research into microbiota, infectious diseases, and nutrition with an emphasis on future research directions.